2022
DOI: 10.3390/jcm11216578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prevalence of Sarcopenia in Patients with Moderate to Severe COVID-19

Abstract: Background: The purpose of this study was to investigate the effectiveness and clinical outcomes of inpatient rehabilitation for patients with severe COVID-19 in Japan. Methods: Patients with severe COVID-19 who underwent rehabilitation during hospitalization were included. The Medical Research Council (MRC) score and short physical performance battery (SPPB), such as physical function assessment and the intensive care unit (ICU) mobility scale, the functional status score for the ICU, and Barthel index as act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Sarcopenia was reported to be in connection with the increasing severity and morality of COVID-19 [18] . A few studies suggested that patients infected with COVID-19 had a higher incidence of sarcopenia, which varies among patients infected with different types of COVID-19 [19,20] . Patients in ICU who had COVID-19 were inclined to be diagnosed with sarcopenia, compared to other patients hospitalized for COVID-19 [20,21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia was reported to be in connection with the increasing severity and morality of COVID-19 [18] . A few studies suggested that patients infected with COVID-19 had a higher incidence of sarcopenia, which varies among patients infected with different types of COVID-19 [19,20] . Patients in ICU who had COVID-19 were inclined to be diagnosed with sarcopenia, compared to other patients hospitalized for COVID-19 [20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies suggested that patients infected with COVID-19 had a higher incidence of sarcopenia, which varies among patients infected with different types of COVID-19 [19,20] . Patients in ICU who had COVID-19 were inclined to be diagnosed with sarcopenia, compared to other patients hospitalized for COVID-19 [20,21] . Moreover, the risk of sarcopenia was higher among the patients after severe or moderate COVID-19 infection with prolonged length of hospital stay and invasive mechanical ventilation [22] .…”
Section: Introductionmentioning
confidence: 99%